Balıkçı teknelerinde motor-pervane sisteminin yarattığı titreşimlerin ve gürültü kirliliğinin incelenmesi - Ekren, Hayati (My University, 1993)
Increasing interest has been focussed on the sea and water resources in order to ensure the required sea and water products in the world. Many studies have been made on the determination of the fish region, fishing techniques and fish processing within the fishery activity. However, limited studies have been carried out for deterrnining the levels of the vibration and noise in the fishing boats. As it knows, the vibration and noise is a great problem for the working personals and environment In this respect, a detailed study for determining the levels of the vibration and noise in the fishing boats which will probably be used in the GAP region. The main part of this study includes the results of a project (T3-92-01) which has been carried out at the Department of Mechanical and Production of the Scientific and Technical Research Council of Turkey (TÜBİTAK). At initial stage, the investigation of the stability, resistance-power and propulsion of a fishing boat and the selection of the propeller of a fishing boat which can be used in the lakes have been made. Secondly, the maximum noise-level has been analyzed considering the noise effects of engine and exhaust and a new exhaust system has been designed in order to minimize the level of the noise according to the ISO standards. As a result, a noise level lower than the noise of engine-speed system has been obtained according to the ISO standards. The exhaust system of the engine (Capacity: 165 HP) which has been used in the experimental investigation has not occurred an effective vibration. Thirdly, the vibrations of propeller and naturel frequencies of the boat have been investigated and undesired effects for human health have not been determined. In this study, an engine and a propeller have been used within a project carried, out of the TÜBİTAK ( No: T3-92-01, "The Optimization of Fishing Boats Suitable for GAP* Waters" ) and this study will have a basic role in the investigation of the engine-power, propeller system and boat forms. Consequently, the vibrations of the engine and propeller system have been investigated and a damper has been used in order to minimize these vibrations. (*) : GAP means that " Southeastern Anatolia Project "
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1993
Keywords: Balıkçı tekneleri; Motor pervane sistemi; Titreşimler ve gürültü kirliliği